PENGARUH VARIASI GRADASI AGREGAT (SLAG) TERHADAP KUAT TEKAN, POROSITAS DAN KUAT TARIK BELAH BETON - . Basid, Abd; W, Yusuf (Department of Civil Engineering, Faculty of Engineering, University of Muhammadiyah Malang, 2014)
PENGARUH VARIASI GRADASI AGREGAT (SLAG)TERHADAP KUAT TEKAN, POROSITAS DAN KUAT TARIKBELAH BETONAbd. Basid1, Yusuf W21,2Jurusan Teknik Sipil Fakultas Teknik Universitas Muhammadiyah MalangAlamat korespondensi : Jalan Raya Tlogomas 246 Malang 65144ABSTRACTThe use of slag as aggregate is quite reasonable because the waste slag is one that has not beenexploited well, in addition to the waste in the waste, slag also categorized tixic and hazardous waste(B3). So, find the solution of the existing problems such as slag used as aggregate in concretemixes. This research was to determine the effect of variety in slag aggregate gradations oncompression strength, porosity and tensile strength of concrete side with up and down 7% fromfuller curve at 28days. From the test result obtained by the maximum compression strength of theconcrete with slag aggregate gradation that occurs at gradation III above fuller curve for 36,99Mpa, while the maxsimum tensile strength sides also occurs in gradation III in the amount of 32,55Mpa and for testing the minimum porosity derived porosity also occurs in gradation III is at 2,42%.The result of testing the mechanical properties of concrete at 28 days showed that there wasinfluence by variety in the strength of slag aggregate concrete. That the more subtle gradations onaggregate become the concrete more dense and has good quality.Key Words : Concrete, Variety, Slag Anggregate